2015
DOI: 10.1002/ajmg.a.37502
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance in Mowat–Wilson syndrome

Abstract: Mowat-Wilson syndrome (MWS) is a multiple congenital anomaly syndrome caused by a heterozygous mutation or deletion of the ZEB2 gene. It is characterized by a distinctive facial appearance in association with intellectual disability (ID) and variable other features including agenesis of the corpus callosum, seizures, congenital heart defects, microcephaly, short stature, hypotonia, and Hirschsprung disease. The current study investigated sleep disturbance in people with MWS. In a series of unstructured intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
(91 reference statements)
1
14
0
Order By: Relevance
“…In the present sample, behavioral symptoms were present in 39.1% of individuals with MWS which is similar to the rates of Evans et al (33.3%) in a comparable group (Evans et al, 2012). These psychological symptoms were also related to sleep problems (Evans et al, 2016). In the present study no significant associations between psychological symptoms and incontinence were found, in contrast to other genetic syndromes with mild ID (Noonan, Williams, Fragile-X-Syndrome) .…”
Section: Behavioral Problemssupporting
confidence: 88%
See 1 more Smart Citation
“…In the present sample, behavioral symptoms were present in 39.1% of individuals with MWS which is similar to the rates of Evans et al (33.3%) in a comparable group (Evans et al, 2012). These psychological symptoms were also related to sleep problems (Evans et al, 2016). In the present study no significant associations between psychological symptoms and incontinence were found, in contrast to other genetic syndromes with mild ID (Noonan, Williams, Fragile-X-Syndrome) .…”
Section: Behavioral Problemssupporting
confidence: 88%
“…Further descriptions of MWS point out the happy demeanor, sociability and frequent laughter, but also selfinjuring and hyperactive behavior (Adam, Justice, Bean, & Fernhoff, 2008;. Sleep disturbances with an association to psychological problems are also found in MWS (Evans, Mowat, Wilson, & Einfeld, 2016). Intelligence in MWS is mostly in the range of severe ID (Evans et al, 2012;.…”
Section: Behavioral Phenotype Of Mowat-wilson Syndromementioning
confidence: 99%
“…Evans et al studied sleep disturbances with the administration of the “Sleep Disturbance Scale for Children” (SDSC) questionnaire [ 70 ]. They found a high level of sleep disturbance in MWS patients, with the highest scores on the Sleep–Wake transition disorders subscale (91% of patients reaching at least the borderline score).…”
Section: Neurological Involvement Of Mwsmentioning
confidence: 99%
“…They suggested that SDSC could be considered an instrument to evaluate and monitor sleep in the syndrome [ 64 ]. Both studies emphasized the importance of screening for sleep disorders and their potential treatment, such as melatonin, benzodiazepines, or niaprazine [ 64 , 70 ].…”
Section: Neurological Involvement Of Mwsmentioning
confidence: 99%
“…Faleiros‐Castro and Paula (2013) included feedback from individuals with intellectual disabilities during the development of the data collection tools. Evans et al (2016) invited professionals working with individuals with an intellectual disability to review the results to verify the themes drawn from focus groups. No other research studies reviewed involved individuals, their carers/family or professionals working directly with the researchers to verify results for credibility.…”
Section: Critical Review Of the Literaturementioning
confidence: 99%